Pengaruh Pertumbuhan Earning Per Share dan Pertumbuhan Perusahaan terhadap Kenaikan Harga Saham BUMN di JII - Iskandar, Ghina Salsabilla (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the effect of Earning Per Share growth and Company growth on the increase in share prices of State-Owned Enterprises for the period 2018 to 2022 simultaneously or partially. This study uses a quantitative method using panel data regression. The sampling technique uses a purposive sampling technique which produces 3 State-Owned Companies listed on the Jakarta Islamic Index for the period 2018 to 2022. The data used is secondary data by compiling the company's financial statements for 2018 to 2022. The results show that the growth in earnings per share and company growth has a positive and significant relationship to the increase in stock prices either partially or simultaneously.